Railway overhead contact wire monitoring system by means of FBG sensors - Erwin Ciro Zuleta; Carla Lupi; Ferdinando Felli; Claudio Paris; Cristian Vendittozzi (Fracture and Structural Integrity)
Safety of infrastructures represents one of the most significant concerns for governments and service providers to preserve people's well-being. One of the main ways to keep in safe facilities (buildings, bridges, railways, etc.) involves the use of monitoring sensor systems in charge of measuring critical operating conditions. Those measurements together with periodical maintenance, contribute to minimize potential risks that the infrastructure faces. The paper aims at designing, developing, and testing a monitoring system for mechanical stresses acting on the overhead contact wire (OCW) to ensure the operational safety of the railway network. In this regard, the paper proposes two Fiber Bragg Grating (FBG) sensors-based solutions, relying on the ability of these sensors to allow real-time and continuous data acquisition. The first one consists in a polyimide-coated sensor bonded on an OCW clamp, the second one is a copper-coated sensor hanging between the two separated halves of an OCW clamp. Significant results have been obtained mechanically testing both solutions, trying to simulate the operative conditions.